JENIS TUMBUHAN DAN KONDISI HUTAN MANGROVE DI NUSA LEMBONGAN DAN NUSA CENINGAN, KECAMATAN NUSA PENIDA, KABUPATEN KLUNGKUNG - I G. A. Sugi Wahyuni; N. M. Susun Parwanayoni; Joko Wiryatno (Bumi Lestari Journal of Environment)
This research was undertaken in Nusa Lembongan and Nusa Ceningan, District ofNusa Penida, Klungkung Regency, between 2005-2006. This reserach was aimed to find outthe size of area and the status of mangrove forest, kind of species, as well as problems facedby the forest related to its conservation status. From this research it was revealed that thesize of the area where the mangrove available in Nusa Lembongan was around 212 ha, andthere was also mangrove forest in Nusa Ceningan about 15 ha. There were 13 species offlora available on mangrove ecosystem which were classified as true mangroves, while 9kinds were asociated mangroves. From the field observation it was revealed that there is apossible threat to the mangrove forest if there is no good management strategy. Someactivities which were available on the mangrove forest that were potentially provided impactsto sustainability of the forest, such as the use for anchoring boats and mangrove touractivities.